2023
DOI: 10.1186/s13195-022-01118-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-6, sAXL, and YKL-40 as systemic correlates of reduced brain structure and function in Alzheimer’s disease: results from the DELCODE study

Abstract: Background Neuroinflammation constitutes a pathological hallmark of Alzheimer’s disease (AD). Still, it remains unresolved if peripheral inflammatory markers can be utilized for research purposes similar to blood-based beta-amyloid and neurodegeneration measures. We investigated experimental inflammation markers in serum and analyzed interrelations towards AD pathology features in a cohort with a focus on at-risk stages of AD. Methods Data of 74 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…In a broader perspective and in concordance with our results, monocyte-derived macrophages have been shown to appear concurrent with the loss of tissue-resident macrophages in several tissues including the liver, brain, lungs, and heart, during events of sustained tissue damage ( 56 , 57 ). Damage in these same tissues (cirrhosis, Alzheimer’s disease, pneumonia, and heart failure) has also been directly linked to increased levels of sAXL ( 53 , 58 60 ). This suggests that an elevated sAXL level serves as an indicator of ongoing tissue damage that initially depletes tissue-resident macrophages, leading to their replacement by monocyte-derived macrophages, which regrettably are unable to resolve the sustained tissue damage and resultant inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader perspective and in concordance with our results, monocyte-derived macrophages have been shown to appear concurrent with the loss of tissue-resident macrophages in several tissues including the liver, brain, lungs, and heart, during events of sustained tissue damage ( 56 , 57 ). Damage in these same tissues (cirrhosis, Alzheimer’s disease, pneumonia, and heart failure) has also been directly linked to increased levels of sAXL ( 53 , 58 60 ). This suggests that an elevated sAXL level serves as an indicator of ongoing tissue damage that initially depletes tissue-resident macrophages, leading to their replacement by monocyte-derived macrophages, which regrettably are unable to resolve the sustained tissue damage and resultant inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of IL-6 were also detected in AD [22], and IL-6 trans-signaling was linked with cognitive deterioration in AD [23]. Another study showed a negative correlation between serum IL-6 levels and the volumetric measures within the Braak region, whereas no such correlation was observed between IL-6 levels in the CSF and possible atrophic changes in this region [24]. Interestingly, IL-1 was over-expressed in AD brains [25,26], with the mechanism interpreted as leading to plaque formation and an increase in acetylcholinesterase [25].…”
Section: Cerebrospinal Levels Of Total Taumentioning
confidence: 99%
“…Children with ASD who have gastrointestinal symptoms are often associated with increases in many innate (IL-1α, TNFα, GM-CSF, IFNα) and adaptive cytokines (IL-4, IL-13, IL-12p70) ( 112 ). IL-6 is a neurogenic cytokine that affects neuronal proliferation, synapse formation, differentiation, and migration and acts as a modulator of central neural pathways, which are important for cognitive functioning ( 113 ), and has also been associated with worsening of restricted and repetitive behaviors ( 114 ). TNF-α has homeostatic functions, such as regulating neurogenesis, myelin formation, blood-brain barrier permeability and synaptic plasticity, and mediates changes in excitatory and inhibitory neurotransmission in a concentration-dependent manner ( 115 ).…”
Section: Neuroinflammation and Immunitymentioning
confidence: 99%